A dual-process model of affective and instrumental attitudes in predicting physical activity. (May 2021) - Phipps, Daniel J.; Hannan, Thomas E.; Rhodes, Ryan E.; Hamilton, Kyra
Abstract: Introduction: A novel dual-process model based upon the affective-reflective theory which distinguishes between affective attitude and instrumental attitude at an explicit and implicit level was used to predict physical activity. Method: Undergraduate students ( N  = 114) completed a lab-based study at two time-points, spaced two weeks apart. Participants completed self-report measures of the theory of planned behavior constructs, including explicit affective attitude and explicit instrumental attitude. Implicit affective attitude and implicit instrumental attitude were measured using single category implicit association tests. Results: Explicit affective attitude and perceived behavioral control indirectly predicted physical activity through intention, and explicit affective attitude, implicit affective attitude, and intention predicted physical activity directly with a modest effect size ( R 2  = 0.24). Discussion: Findings suggest explicitly and implicitly held evaluative information are conceptually distinct, and affective evaluations are key in guiding physical activity behavior regardless of whether such evaluations are implicit or consciously accessible. Highlights: A dual-process model was used to predict physical activity. Attitude was assessed as affective and instrumental explicit and implicit evaluations. Intention, explicit affective attitudes, and implicit affective attitudes predicted physical activity directly. Perceived behavioral control and explicit affective attitudes indirectly predicted physical activity through intention. Neither implicit instrumental attitudes nor explicit instrumental attitudes predicted physical activity.